Co (jeszcze) wynika z „odkrycia” znaczenia Europy Środkowo-Wschodniej dla historii architektury nowoczesnej pierwszej połowy XX wieku? - Makała, Rafał (Artium Quaestiones, 2025)
The history of modern architecture was largely written in the mid-20th century from a Western perspective (i.e. Western Europe and North America), serving to construct the myth of the “International Style”. According to influential figures such as N. Pevsner and S. Giedion, the decisive role in its emergence was attributed to a group of French architects led by Le Corbusier, Dutch creators, and the Bauhaus. Of particular interest was the elevation of the latter to the foremost position in the avant-garde (ideologically “transposed” from central Germany to the West), carried out by W. Gropius in the 1930s and 1940s, beginning with the 1932 MoMA exhibition. Research on the “Bauhaus myth”, undertaken from the mid-20th century onward (e.g. by W. Nerdinger), challenged this image. Nevertheless, the image of modernist architecture continues to be shaped in a way that canonizes the Western European avant-garde together with the Bauhaus, a narrative reinforced by the widely celebrated centenary of the school’s founding in 2019. As a result, modern architecture from the first half of the 20th century is still discussed in terms derived from the paradigms of the Western European avant-garde, using the terminology created to describe it. The growth of research and publications after 1989 on the architecture and art. theory of Central and Eastern Europe in the first half of the 20th century has not fundamentally altered this view. This may have been partly the result of language barriers, though not in the case of the Wrocław scholarly milieu, for instance. This example suggests that the history of modern architecture is still perceived through a Cold War–era perspective that emphasizes Western dominance. It should therefore be reconceived in order to reveal its complexity and, at the same time, to abandon the evaluative terminology that relegates entire currents to a subordinate position (e.g. “conservative modernism”). Such a rethinking should be accompanied by reflections on the significance of Central and Northern Europe, both in the field of architectural theory and in practice. This would allow for a better understanding of trends and phenomena that, within the traditional model, were consigned to the margins of the “mainstream”, equated with the avant-garde of Neues Bauen.